2009
DOI: 10.1007/s12178-009-9044-9
|View full text |Cite
|
Sign up to set email alerts
|

Coracoid impingement syndrome: a literature review

Abstract: Coracoid impingement syndrome is a less common cause of shoulder pain. Symptoms are presumed to occur when the subscapularis tendon impinges between the coracoid and lesser tuberosity of the humerus. Coracoid impingement should be included in the differential diagnosis when evaluating a patient with activity-related anterior shoulder pain. It is not thought to be as common as subacromial impingement, and the possibility of the coexistence of the two conditions must be taken into consideration before treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 19 publications
1
48
0
2
Order By: Relevance
“…The most related cause of anterior shoulder pain is subcoracoid impingement syndrome, defined as the encroachment of the posterolateral coracoid process upon the lesser tuberosity of the humerus [6], causing a compression of soft tissues, such as the subscapularis tendon, glenohumeral joint capsule and subcoracoid bursa, and occasionally the long head of the biceps tendon [7]. Anatomic differences for humerus lesser tuberosity and coracoid process [6, 8], as well as anteversion and internal humeral rotation [7], and a history of chronic overuse of persisted flexion, adduction and internal rotation shoulder positions [9], have also been established as possible causes of anterior shoulder pain.…”
Section: Introductionmentioning
confidence: 99%
“…The most related cause of anterior shoulder pain is subcoracoid impingement syndrome, defined as the encroachment of the posterolateral coracoid process upon the lesser tuberosity of the humerus [6], causing a compression of soft tissues, such as the subscapularis tendon, glenohumeral joint capsule and subcoracoid bursa, and occasionally the long head of the biceps tendon [7]. Anatomic differences for humerus lesser tuberosity and coracoid process [6, 8], as well as anteversion and internal humeral rotation [7], and a history of chronic overuse of persisted flexion, adduction and internal rotation shoulder positions [9], have also been established as possible causes of anterior shoulder pain.…”
Section: Introductionmentioning
confidence: 99%
“…It is often only appreciated when patients have persistent pain, possibly even after subacromial decompression for rotator cuff disease has been performed with no relief of symptoms. Orthopaedic surgical studies have demonstrated that the location of the coracoid tip affects the shape of the subcoracoid outlet [1]. Different shapes have been described but in particular a Bchevron^-shaped outlet in which the coracoid tip lies inferior to the supraglenoid tubercle has been shown to correlate surgically with subcoracoid impingement and entrapment of the subscapularis tendon ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, coracoid impingement refers to impingement of the subscapularis and/or adjacent soft tissues between the coracoid process and the lesser tuberosity. Although coracoid impingements are rare, it is important to differentiate them from other types of SIS since they usually require surgical treatment (Okoro et al, 2009). The types of SIS described above are classified based on the location of the impingement.…”
Section: Discussionmentioning
confidence: 99%